Bitterness quenching quick-setting microcapsule and preparation method thereof
By constructing bitter quenching quick-coagulation microcapsules coated with gel polysaccharide dry powder, the problem of bitter taste exposure in children and the elderly when taking bitter Chinese medicine solid preparations is solved, and the ideal taste masking effect of the drug powder in water and mouth is achieved, and the compliance of medication is improved.
Patent Information
- Application Number
- CN202411956813.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-04-01
AI Technical Summary
Children and the elderly and other dysphagia groups are difficult to avoid bitter taste exposure when taking the solid preparation of bitter Chinese medicine, which leads to a decrease in the compliance with the medication.
By coating the gel polysaccharide dry powder on the surface of bitter medicine, a bitter quenching quick coagulation microcapsule is constructed, and micronized κ-carrageenan is used as the capsule material to achieve the ideal taste masking effect of the drug powder in water-mouthed.
It significantly reduces the bitterness of the mouth, peak bitterness and aftertaste of the drug, improves the patient's medication compliance, and does not affect the normal release of the drug in the stomach and efficacy.
Smart Images

Figure CN119732925A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bitter quenching quick-setting microcapsule, belonging to the field of pharmaceutical preparations. Background Art
[0002] Oral administration is currently the most commonly used treatment method in clinical practice, but taking solid preparations is a common problem for people with swallowing difficulties, such as children and the elderly. In order to improve medication compliance, solid preparations such as tablets or capsules are usually broken or ground before taking to reduce the difficulty of swallowing and the risk of choking. However, one of the problems with this method is that it will cause the bitter taste of the drug to be exposed, especially for traditional Chinese medicine preparations, which will significantly reduce the patient's medication compliance.
[0003] Tablets are one of the mainstream dosage forms of solid preparations of traditional Chinese medicine, and are also relatively common in children's medicines. According to a search of the Yaozhi.com database, there are 52 tablets of Chinese patent medicines for children or Chinese patent medicines for adults and children on the market, including the current edition of the "Chinese Pharmacopoeia" (Part I), Xiaoer Jindan Tablets, Xiaoer Xishi Tablets, Xiaoer Qingfei Zhike Tablets, Xiaoer Xieli Tablets, Xiaoer Jiegan Tablets, etc. In order to mask the bitterness or other unpleasant taste of the drug, the pharmaceutical industry has formed a mature sugar coating or film coating technology. However, tablets are not suitable for children to swallow directly, and there is a certain risk of choking. To make it easier for children to take, clinical pharmacists usually grind the tablets into powder and ask parents to give them to children with water or sugar water, fruit juice, etc. However, this method destroys the tablet coating layer, causing the drug powder to be exposed to water, and a large amount of bitter components are dissolved. Even if sweeteners such as sugar water and fruit juice are added, bitter and sweet coexist. The sour components contained in the juice will also enhance children's perception of bitterness. In addition, some drug powder remains in the mouth, causing a strong sense of grit and a lingering bitter taste, which requires a lot of water to rinse the mouth. This painful feeling of taking medicine has become a lingering shadow for many children.
[0004] In recent years, microtablets (also known as mini tablets) have become one of the important directions for the improvement and innovation of children's tablets. The diameter of microtablets is less than 3mm, and they have the advantages of ordinary tablets and micropellets, which are easy to swallow. Even infants and young children can swallow a single microtablet; microtablet coating can also achieve taste masking and localized drug release functions; microtablets can be used directly, or made into capsules or large tablets. However, the preparation technology of microtablets is relatively complex, the drug loading is low, and the fit between the punch and the die hole and the flowability and filling properties of the drug powder are key factors affecting production. At present, there are already marketed products of microtablets in chemical drugs, including pancreatin microtablets, ferrous sulfate microtablets, etc.; but no traditional Chinese medicine microtablets have been successfully developed and marketed, which is closely related to the complex physical properties of crude Chinese medicine or native powder and the large dosage. Therefore, it is urgent to explore new ideas for taste masking and molding of traditional Chinese medicine children's tablets. Summary of the invention
[0005] Based on the concept of replacing tablet coating with powder coating, the present invention proposes to construct bitter quenching quick-setting microcapsules by coating the surface of bitter drugs with dry powder of gelatin polysaccharide, so as to achieve the ideal taste-masking effect of drug powder in water and mouth, and solve the difficulty of patients taking medicine.
[0006] The invention provides a bitter quenching quick-setting microcapsule, which is formed by using a bitter drug containing -OH as a capsule core, a thin oil layer in the middle, and micro-κ-Car as a quick-setting microcapsule material for coating.
[0007] Among them, the bitter drugs containing -OH include notoginseng total saponins, berberine, quercetin, naringin, limonin, and momordica charantia.
[0008] The oil layer is olive oil, camellia oil, corn oil, rapeseed oil, soybean salad oil and peanut oil.
[0009] It uses powder modification technology and particle design technology to coat the gel powder coating material on the surface of drug powder to construct quick-setting microcapsules.
[0010] The bitter drug is Panax notoginseng total saponin; the oil is olive oil; the weight ratio of Panax notoginseng total saponin, olive oil and micro-κ-Car is:
[0011] 300 parts of Panax notoginseng total saponins, 7.5-15 parts of olive oil, and 180-300 parts of micro-κ-Car.
[0012] Preferably, the weight ratio of Panax notoginseng total saponins, olive oil and micro-κ-Car is:
[0013] 300 parts of Panax notoginseng total saponins, 7.5 parts of olive oil, and 180 parts of micro-κ-Car.
[0014] The present invention also provides a method for preparing the bitter quenching quick-setting microcapsules, which comprises the following steps:
[0015] a. Take Panax notoginseng total saponins and olive oil, add them into a vibrating grinding hopper, and grind and coat for 3 minutes;
[0016] b. Add the inclusion complex PNS-OLI and micro-κ-CAR prepared in step a into a vibrating grinding hopper, grind and coat for 6-18 minutes, and obtain bitter quenching rapid-setting microcapsules.
[0017] Wherein, the amount of olive oil used in step a is 2.5%-5% of the total amount of Panax notoginseng saponins and olive oil;
[0018] The dosage ratio of PNS-OLI and micro-κ-CAR described in step b is: 1:(0.5-1); the grinding time is 15 minutes.
[0019] The amount of olive oil used is 2.5% of the total amount of Panax notoginseng saponins and olive oil; the dosage ratio of PNS-OLI and micro-κ-CAR described in step b is 1:0.6.
[0020] The vibration mill coating conditions are as follows: the machine operating temperature is -5°C, an appropriate amount of liquid nitrogen is added, the medium filling rate is 70%, the diameter is 21mm, and the columnar stainless steel medium has an amplitude of 6mm.
[0021] The invention also provides an oral preparation containing the bitter quenching quick-setting microcapsule.
[0022] The oral preparations are tablets, powders, capsules and pills.
[0023] Quick-gel microcapsules are a new type of taste-masking microparticles formed by encapsulating bitter drugs with gelatin powder. The structure of the microcapsules after contact with water is bionic designed from passion fruit seeds ( Figure 1 ). The surface gel layer encapsulates the bitter drug inside and isolates it from water, achieving the purpose of physically shielding the bitter taste. Therefore, the gel polysaccharide powder (capsule material) needs to gel quickly when it comes into contact with water, swell to a limited extent without dissolving, and form a gel barrier layer on the surface of the drug (capsule core) to prevent the drug from dissolving and exposing the bitter taste. In addition, the gel polysaccharide capsule material must also meet the requirements of not degrading in water-mouth to mask the bitter taste of the drug, and not affecting the normal efficacy of the drug when degraded in the stomach. In order to meet the above two conditions at the same time, the present invention selects κ-carrageenan as the target object of the rapid-setting microcapsule capsule material from many commonly used gel polysaccharide materials (such as carrageenan, sodium alginate, chitosan, xanthan gum, etc.), and the reasons are as follows.
[0024] κ-Carrageenan (κ-Car), a natural high molecular linear sulfate polysaccharide, is also an anionic polysaccharide. First, as a hydrophilic colloid, κ-Car has the gel property of being insoluble in cold water, but being able to absorb water and swell into a gel. Its unique gel property can meet the requirements of the quick-setting microcapsule material for swelling into a gel by absorbing water, but it cannot achieve rapid gelation when exposed to water. To this end, the inventors conducted a micronization modification study on κ-Car in the early stage, and for the first time confirmed that micronization can accelerate the speed and degree of water absorption and swelling of κ-Car powder, as well as improve the gel properties, swallowing properties and bitterness suppression of κ-Car. Secondly, κ-Car powder has strong stability, and the dry powder is not easy to degrade after long-term storage. It is also very stable in neutral and alkaline solutions, and will not hydrolyze even if heated. However, in acidic solutions (especially pH ≤ 4.0), carrageenan is prone to hydrolysis, which is due to the breakage of the 3,6-anhydro-D-galactose connection in the chemical structure of carrageenan at low pH values. Therefore, κ-Car can achieve the purpose of not degrading in water-mouth, but degrading in the stomach. Finally, and most importantly, κ-Car also has the effect of suppressing bitterness and masking taste. Studies have shown that it can not only be used as a hydrogel bead wall material to effectively mask the bitterness of caffeine, but also reduce the bitterness of quercetin through the electrostatic induction effect. This makes the quick-setting microcapsules have the potential to suppress bitterness by both physical shielding and electrostatic induction. Based on the improvement of the gel properties and taste-masking effect of κ-Car by micronization modification, the present invention selects micronized κ-Car (micro-κ-Car) as the capsule material for encapsulating bitter drugs to construct quick-setting microcapsules, so as to achieve the purpose of swelling and suppressing bitterness in the water-mouth of the taste-masking particles, and reducing the taste of drugs in the stomach.
[0025] Panax Notoginseng Saponins (PNS) is the main active ingredient of Panax notoginseng and the material basis of its bitter taste. Ginsenoside Rg1, ginsenoside Rb1 and ginsenoside Rd contained in it are the main contributors to the bitter taste of Panax notoginseng. It is worth noting that the property of PNS being easily soluble in water makes its bitterness fully exposed in the oral cavity, and the bitterness is strong and lasting from the entrance to the aftertaste, which significantly reduces the medication compliance of PNS. Therefore, the present invention selects PNS as a representative bitter drug, and improves the palatability of PNS and its preparations by constructing quick-setting microcapsules, thereby improving the medication compliance of patients. In addition, in order to avoid the sudden release of bitterness of PNS fine powder that is not completely encapsulated when it encounters water, and inspired by the hydrogel microcapsules containing a thin oil layer, the present invention intends to first use olive oil (OLI) to encapsulate PNS, aiming to reduce the content of PNS fine powder, improve the encapsulation efficiency of PNS, and avoid its sudden release of bitterness. Afterwards, micro-κ-Car is used to dry-powder coat the PNS containing a thin oil layer to avoid the introduction of water or organic reagents, which would cause the PNS to dissolve and expose the bitter taste. However, there are certain technical difficulties in coating the surface of the drug powder with the gelatin powder material. Because the gelatin powder is a high-toughness material with strong resistance to external shear and crushing, it is difficult to crush and refine it to meet the assembly requirements of the core-shell structure. At the same time, the κ-Car powder is rod-shaped or block-shaped, with a large particle size and poor uniformity. It is difficult to coat the drug surface through particle design, and it needs to be pre-treated to reduce the particle size and achieve uniform particle size. In the early stage, the research group has successfully micronized the κ-Car particle size from 150μm to about 15μm through liquid nitrogen cryogenic cooling combined with silica grinding and dispersion, solving the problems of large powder particle size and poor uniformity, so as to meet the assembly requirements of the core-shell structure of the quick-setting microcapsule.
[0026] In summary, the present invention will use PNS as the bitter drug in the capsule core, OLI as the intermediate thin oil layer, and micro-κ-Car as the quick-setting microcapsule material. It is intended to coat the gel powder coating material on the surface of the drug powder through powder modification technology and particle design technology to construct PNS-OLI-κ-Car quick-setting microcapsules, thereby masking the bitter taste of PNS in the water-mouth and improving the patient's medication compliance. The present invention will use taste evaluation as an indicator to optimize the formula ratio and preparation process of PNS-κ-Car quick-setting microcapsules. Afterwards, the structure and performance of PNS-OLI-κ-Car quick-setting microcapsules will be characterized, and its dual bitterness suppression potential will be verified to clarify the bitterness suppression and taste masking mechanism of quick-setting microcapsules. The present invention hopes to improve the shortcomings of traditional solid preparations in taste and swallowing through the quick-setting microcapsules, a new bitterness suppression and taste masking preparation, and can be prepared into various oral preparations to solve the common problem of difficulty in taking medicine faced by children, the elderly and other groups with sensitive taste and difficulty in swallowing. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1.Bionic design structure diagram of quick-setting microcapsule;
[0028] Figure 2 .Taste evaluation by volunteers (A and B) and electronic tongue test results (C). PNS: total saponins of Panax notoginseng; a: PNS: 2.5% OLI; b: PNS: 5% OLI; cg: PNS-OLI-CAR obtained by mixing PNS-OLI:CAR at a ratio of 1:0.5, 1:0.6, 1:0.7, 1:0.8 and 1:1; 1-5: samples obtained by grinding and encapsulating PNS-OLI-CAR in a vibration mill for 6, 9, 12, 15 and 18 min;
[0029] Figure 3 In vitro cumulative dissolution rates of PNS and PNS-OLI-CAR in water (A), pH 1.2 (B), and pH 6.4 (C), as well as the average particle size and particle size distribution of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR (D and E), and the absorption isotherm of the four powders in water (F);
[0030] Figure 4 .Appearance of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR;
[0031] Figure 5 .Stability parameters (A and B) and transmitted light images of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR (C: PNS, D: micro-κ-CAR, E: PNS-OLI, F: PNS-OLI-CAR);
[0032] Figure 6 .Microstructures of PNS (A), micro-κ-CAR (B), PNS-OLI (C), and PNS-OLI-CAR (D). (A and B: under fluorescence conditions; C and D: under bright field conditions ×40);
[0033] Figure 7 .SEM and EDS elemental scans of PNS (A), micro-κ-CAR (B), PNS-OLI (C), and PNS-OLI-CAR (D);
[0034] Figure 8 .Full scan spectra of FTIR (A), Raman (B), DSC (C) and XPS (D) elemental analysis of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR;
[0035] Fig. 9 High-resolution XPS spectra of C1s, O 1s, and S2p in PNS (A), PNS-OLI (B), micro-κ-CAR (C), and PNS-OLI-CAR (D);
[0036] Fig.10 .AFM images and 3D surface roughness of PNS (A), micro-κ-CAR (B), PNS-OLI (C), and PNS-OLI-CAR (D);
[0037] Fig.11 .Electrostatic potential, binding sites, binding energy and Gibbs free energy of Rg1, Rb1 and Rd with κ-CAR in PNS. DETAILED DESCRIPTION
[0038] Example 1 Preparation process of the quick-setting microcapsule PNS-OLI-CAR of the present invention
[0039] 1 Materials
[0040] PNS and OLI were purchased from Xi'an Shennong Biotechnology Co., Ltd., κ-Car was purchased from Henan Mingxuan Food Co., Ltd., and Panax notoginseng total saponin reference substance was purchased from Chengdu Desite Biotechnology Co., Ltd.
[0041] κ-Car and 15% silicon dioxide were put into the hopper of a vibration mill (SYFM-8II vibration type ultrafine pulverizer, Jinan Songyue Machinery Co., Ltd.) for co-grinding to obtain micro-κ-Car.
[0042] Preparation process of 2PNS-OLI-CAR
[0043] 7.5 g and 15 g of OLI and 300 g of PNS were added into the hopper of a vibration mill (instrument model) respectively, and PNS-2.5% OLI and PNS-5% OLI were prepared after grinding and coating for 3 minutes.
[0044] Under the premise of ensuring that the drug loading of PNS is not less than 50%, the coating effect of different amounts of micro-κ-CAR on PNS-OLI was investigated. PNS-OLI and micro-κ-CAR at a ratio of 1:0.5, 1:0.6, 1:0.7, 1:0.8 and 1:1 were added to the vibration mill hopper, and PNS-OLI-CAR samples with different ratios were obtained after grinding and coating for 12 minutes. Afterwards, based on the fixed optimal ratio, the effect of vibration mill coating time on the coating effect was investigated, and PNS-OLI-CAR samples coated for 6 minutes, 9 minutes, 12 minutes, 15 minutes and 18 minutes were obtained.
[0045] The vibration mill coating conditions are: the machine operating temperature is -5°C, an appropriate amount of liquid nitrogen is added, the medium filling rate is 70%, the diameter is 21mm, and the columnar stainless steel medium has an amplitude of 6mm.
[0046] Example 2 Taste evaluation, drug loading and dissolution, powder properties, structural characterization, and quantum chemical detection tests of the quick-setting microcapsules of the present invention
[0047] 1. Experimental Methods
[0048] 1. Taste evaluation
[0049] 1.1 Volunteer Evaluation
[0050] Screening of volunteers: aged 20 to 28 years old, no severe allergies, genetic history, cholecystitis, oral and pharyngeal diseases, no bad habits such as smoking and drinking, and normal taste. Quinine sulfate solutions with different concentration gradients were used to train the volunteers on taste evaluation standards to familiarize them with the scoring standards: 0mg / ml, 0.05mg / ml, 0.3mg / ml, 0.5mg / ml, and 1mg / mL quinine sulfate solutions corresponded to bitterness scores of 0 (no bitterness), 2.5 (slightly bitter), 5 (obvious bitterness), 7.5 (severe bitterness), and 10 (intense bitterness). Volunteers were asked to remember the bitterness perception and corresponding scores corresponding to the 5 concentration gradients of quinine sulfate solutions. Subsequently, a single-blind test was conducted, and 2 sample solutions were randomly selected from the 5 bitter solutions for the volunteers to taste. If the answer was correct, the test was passed. All volunteers voluntarily signed the informed consent form.
[0051] Preparation of oral samples: PNS stock solution, PNS-OLI solutions with different OLI contents, and PNS-OLI-CAR solutions with different dosages and coating times were prepared respectively. The PNS contained in each solution was a single oral dose (100 mg).
[0052] Oral tasting evaluation by volunteers: Visual analogue scoring (VAS) was used to conduct a more detailed sensory evaluation of each sample. Each volunteer took 10-15 mL of sample solution and held it in the mouth, gargling in the mouth so that the tongue and mouth could fully feel the taste of the medicine, and sensory scoring was performed based on the bitterness of the PNS standard solution. It is generally believed that the bitterness of the sample can be fully perceived about 15 seconds after entering the mouth, so the perception intensity at the 15th second of entry was selected as the peak value and scored, and then the medicine was spit out. The scores of the bitterness at the entrance of the sample (0s), peak bitterness (15s) and aftertaste bitterness (60s) were recorded respectively. After that, rinse the mouth with pure water until there is no bitterness in the mouth, and evaluate the next sample after resting for 15-30 minutes.
[0053] 1.2 Electronic tongue evaluation
[0054] Preparation of reference solution: Accurately weigh 2.2365 g potassium chloride and 0.045 g tartaric acid, add 500 mL of distilled water, stir to dissolve, transfer to a 1000 mL volumetric flask, and make up to volume.
[0055] Preparation of positive electrode cleaning solution: Accurately weigh 7.46g potassium chloride, add 500mL of distilled water, stir to dissolve, accurately add 300mL of anhydrous ethanol, add accurately weighed 0.56g of potassium hydroxide while stirring, transfer to a 1000mL volumetric flask after dissolution, and make up to volume.
[0056] Preparation of negative electrode cleaning solution: Accurately measure 300 mL of anhydrous ethanol, shake and mix with 500 mL of distilled water, add 8.3 mL of concentrated hydrochloric acid, stir and mix, then transfer to a 1000 mL volumetric flask and make up to volume.
[0057] Preparation of test samples: PNS stock solutions of different concentrations, PNS-OLI solutions with different OLI contents, and PNS-OLI-CAR solutions with different dosages and coating times were prepared as electronic tongue evaluation samples. The concentration of PNS contained in the samples was 10 mg / ml.
[0058] Electronic tongue test method: The electrode is cleaned in the cleaning solution for 90 seconds, and cleaned twice with the reference solution. The sensor is reset to zero at the equilibrium position for 30 seconds. After reaching the equilibrium condition, the test is started for 30 seconds. The sensor is briefly cleaned in two sets of reference solutions for 3 seconds, and the sensor is inserted into the new reference solution for 30 seconds. The test is repeated 4 times, and the first cycle is removed. The average data of the last 3 times is taken as the test result. (Insent model: Japan, SA-402B)
[0059] 2. Drug loading and dissolution
[0060] 2.1 UV-Vis spectrophotometry of total saponins of Panax notoginseng
[0061] PNS was accurately weighed into 5 mL volumetric flasks, and 70% methanol was added to the scale to obtain reference solutions with concentrations of 5, 3.75, 3.125, 1.875, 0.9375, and 0.625 mg / ml, respectively. The maximum absorption wavelength was measured at 219 nm in a UV-6100 UV-visible spectrophotometer (METASH, Shanghai Yuanxi Instrument Co., Ltd.), and the standard curve was drawn at this wavelength.
[0062] 2.2 Drug loading and encapsulation efficiency
[0063] Preparation of test solution: accurately weigh 50 mg of PNS-OLI-CAR quick-gel microcapsules in a stoppered conical flask (n=3), add 20 ml of a mixed solution of 70% methanol-hydrochloric acid (50:1), stopper, weigh, ultrasonically treat (power 250 W, frequency 40 kHz) for 10 min, cool, make up the loss with a mixed solution of 70% methanol-hydrochloric acid, shake well, centrifuge at 8000 rpm for 5 min, filter, accurately measure 2 ml of the filtrate, place in a 5 ml volumetric flask, add 70% methanol to the mark, shake well, and obtain.
[0064] Preparation of negative sample solution: Take an amount of blank carrageenan equal to 50 mg PNS-OLI-CAR and prepare it according to the method for preparing the test solution.
[0065] Determination method: Determine the absorbance at a wavelength of 219 nm, calculate the PNS content in the test sample according to the above standard curve, and calculate the drug loading and encapsulation efficiency according to the following formulas:
[0066] Drug loading = W1 / W2*100%
[0067] Encapsulation efficiency = W2*drug loading / W3*100%
[0068] Where W1 is the measured PNS content in PNS-OLI-CAR, W2 is the sampling amount of PNS-OLI-CAR, and W3 is the input amount of PNS in PNS-OLI-CAR.
[0069] 2.3 Dissolution
[0070] To calculate the in vitro release rate of PNS, the PNS-OLI-CAR samples were weighed and placed in stoppered conical bottles containing 50 ml of pH 1.2 (simulated gastric fluid, no enzyme), pH 6.8 (simulated intestinal fluid), and pure water, and then placed on a shaker. The conditions were maintained at 100 rpm and 37 ° C. 2 ml samples were taken from each solution at different time intervals and replaced with fresh buffer. Sampling was continued for 2 hours, and the content of PNS in the dissolution medium was determined at a wavelength of 219 nm, the cumulative dissolution was calculated, and the cumulative dissolution curve was drawn.
[0071] 3. Powder properties
[0072] 3.1 Average particle size and particle size distribution
[0073] Mastersizer 2000 laser particle size analyzer (Malvern Instruments Ltd., UK) was used to measure the particle sizes corresponding to 10%, 50% and 90% of the cumulative particle size distribution of the samples under the dry method test, i.e., d (0.1) d (0.5) d (0.9)Each sample was tested three times in parallel. Particle size test parameters: injection air pressure 322.5 kPa, injection speed 80%, shading range 0.5% to 6%, sample measurement time 10 s, background correction time 10 s.
[0074] 3.2 Powder physical properties test
[0075] The bulk density, tap density, angle of repose and dispersion of each powder were measured using the HYL-1001 multifunctional powder physical property tester, and each sample was measured three times in parallel. An appropriate amount of the powder to be tested was placed in a sample tube, heated and blown with nitrogen to constant weight, and then transferred to the ASASP 2460 fully automatic specific surface area and porosity analyzer (McMerritik Instruments Co., Ltd., China) for specific surface area and porosity determination.
[0076] 3.3 Wettability and rapid setting
[0077] 0.5g of PNS-OLI-CAR powder was added to a certain amount of pure water and stirred, and the time required for the powder to be completely wetted was recorded at different temperatures and stirring speeds. Each sample was measured three times in parallel.
[0078] 0.2 g of PNS, CAR, PNS-OLI and PNS-OLI-CAR carrageenan powder were taken in 20 ml of 60°C pure water, and the Turbiscan Lab stability analyzer (Formulaction, France) was used to scan until it settled to the bottom of a cylindrical transparent glass bottle. The first 5 minutes were scanned every 25 seconds, and then every 10 minutes. The transmitted light (T) and stability parameters (Turbiscan stability index, TSI) of the powder in the solution were recorded within 1 hour to track the changes in the time and height of powder dissolution, water absorption and swelling. The TSI value can be reflected in the measurement time. The change in the intensity of the transmitted light of each measurement intersecting the previous measurement is worth accumulating, reflecting the comprehensive changes of the sample during the entire measurement time. The larger the TSI value, the more unstable the system is and the greater the amplitude of the sample change.
[0079] 4. Structural characterization
[0080] 4.1 Optical Microscopy
[0081] The morphologies of the four powders were observed under a Leica DM6 B optical microscope (Germany) under fluorescence or bright field, and the images were processed using LAX S Office software (Germany).
[0082] 4.2SEM and EDS
[0083] Each sample powder was fixed to the sample stage with double-sided conductive adhesive, and after vacuum gold coating by ion sputtering, it was placed under a scanning electron microscope (SEM) for observation and photography. CAR mainly contains elements such as C, O, and S. The mapping mode of the energy spectrometer was used to perform point scanning on the selected area of each sample to analyze the sample elements.
[0084] 4.3 FTIR
[0085] Appropriate amounts of samples were taken and ground with KBr, then pressed into thin slices and analyzed using a Nicolet IS10 (Thermo Fisher Scientific, USA) FTIR spectrometer with a scanning range of 400-4000 cm -1 The resolution is 0.4cm -1 .
[0086] 4.4 Raman spectroscopy
[0087] The Raman spectra of PNS, OLI, CAR, PNS-OLI and PNS-OLI-CAR samples were recorded at 3500 cm-1 using a confocal Raman microscope (Thermo Fisher DXR2, USA) at an emission wavelength of 785 nm. -1 Up to 100cm -1 The signals within the Raman shift range are processed to obtain the Raman spectrum.
[0088] 4.5 Differential Scanning Calorimetry (DSC)
[0089] 10 mg of the sample to be tested was weighed and placed in a blank aluminum crucible and sealed. The DSC curve of each sample was established on a DSC scanning calorimeter (Hitachi DSC7020, Japan) in the temperature range of 50-300°C at a heating rate of 10°C / min, and the nitrogen purge rate was 50 mL / min.
[0090] 4.6 X-ray Photoelectron Spectroscopy (XPS)
[0091] Take an appropriate amount of sample and press it onto the sample plate. Then put the sample into the sample chamber of the Thermo Scientific K-Alpha XPS instrument (USA). The pressure in the sample chamber is less than 2.0×10 -7 mbar, the samples were sent into the analysis room to detect the types and states of different elements on the surface of each sample. The spot size was 400μm, the working voltage was 12kV, the filament current was 6mA; the full spectrum scan energy was 150eV, the step length was 1eV; the narrow spectrum scan energy was 50eV, the step length was 0.1eV.
[0092] 4.7 Atomic Force Microscopy (AFM)
[0093] Part of the sample was dispersed in aqueous solution and vortexed to mix, and then a few drops of the dispersed liquid were added drop by drop on the mica sheet. After drying, the sample was photographed using a Bruker Dimension Icon AFM instrument (Germany) with a scanning range of 10 μm*10 μm and 5 μm*5 μm.
[0094] 5. Quantum Chemistry
[0095] Using PNS as a bitter model substance, quantum chemistry was used to
[0096] The electrostatic potential (ESP) and Gibbs free energy of the binding process between PNS and κ-carrageenan were calculated at the B3LYP-D3(BJ) / 6-31G(d) / CPCM(Water) theoretical level and UFF force field. Structural optimization and energy calculation were performed in the Gaussian 09w program to explore the binding sites of Rg1, Rb1, Rd in PNS and κ-carrageenan.
[0097] Quantum chemical studies were performed using density functional theory (DFT) in the GAUSSIAN 16 software package. Geometry optimization and frequency analysis were calculated under the B3LYP hybrid functional and GD3BJ diffusion correlation of the 6-31G(d) basis set. The bond energy and Gibbs free energy of Rg1, Rb1, Rd(A) and κ-carrageenan (B) in PNS were calculated as follows: E=E(AB)-E(A)-E(B), G=G(AB)-G(A)-G(B). All geometries were optimized in this study, and the 6-31G(d) basis set was used for all elements. 6. Statistical analysis
[0098] Data are presented as mean ± SD, and the determination was repeated at least three times. SPSS software (IBM SPSS Statistics 21, Chicago, USA) was used for one-way ANOVA and t-test, and *p < 0.05 was considered to be significant.
[0099] 2. Results and Discussion
[0100] 1. Taste evaluation
[0101] 1.1 Volunteer Evaluation
[0102] The purpose of constructing quick-setting microcapsules is to reduce / mask the bitter taste of drugs and improve patients' compliance with medication. Therefore, the present invention uses the bitterness score of PNS-OLI-CAR as an indicator and uses the volunteer visual analogue scoring method to evaluate the taste of PNS, PNS-OLI with different amounts of OLI, micro-κ-CAR with different amounts, and PNS-OLI-CAR with different grinding times, in order to screen the optimal dosage ratio of PNS to OLI and CAR, as well as the optimal molding process of PNS-OLI-CAR. The volunteer evaluation results show that ( Figure 2 A), the mean bitterness scores of the PNS solution at 0s, 15s and 60s were 7.5, 7.8 and 6.7, respectively, which belong to the severe bitterness level. The water-soluble nature of PNS makes its bitterness fully exposed in the mouth and water, and the bitterness is strong and lasting from the entrance to the aftertaste. Inspired by the cell structure, the present invention uses OLI to encapsulate PNS, so that a thin oil layer is formed on the surface of PNS to prevent the sudden release of bitterness of PNS when it comes into contact with water. The coating effect of OLI on PNS at 2.5% and 5% dosages was investigated respectively, and the volunteer scoring results showed that the bitterness of PNS-OLI was reduced. The mean bitterness scores of PNS-2.5% OLI solution at 0s, 15s and 60s were 5.7, 5.8 and 4.7, respectively. The mean bitterness scores of PNS-5% OLI solution at 0s, 15s and 60s were 5.3, 5.1 and 4.1, respectively. It can be seen that OLI has a certain masking effect on the bitterness of PNS, which may be because it forms a hydrophobic oil film on the surface of PNS, preventing PNS from dissolving in water and causing the bitterness to be exposed. Although the greater the amount of OLI used, the better the bitterness masking effect, excessive use will increase the viscosity of the powder and cause it to agglomerate into blocks, which is not conducive to the construction of quick-setting microcapsules. Therefore, the present invention selects PNS-OLI with a 2.5% OLI dosage for subsequent research.
[0103] Based on PNS-OLI, micro-κ-CAR was used to dry powder coat it to construct PNS-OLI-CAR quick-setting microcapsules to cover up the bitterness of PNS. The dosage of CAR was screened under the same preparation process conditions, and the bitterness of PNS-OLI and CAR at a ratio of 1:0.5, 1:0.6, 1:0.7, 1:0.8 and 1:1 was scored. The results are shown in Figure 2As shown in A, compared with PNS and PNS-2.5% OLI, the bitterness of PNS-OLI-CAR has decreased to a certain extent, but the bitterness masking effect is not better with the increase of CAR dosage, but it shows a trend of first decreasing and then increasing with the increase of CAR dosage. Among them, at the dosage of 1:0.6, the bitterness score of PNS-OLI-CAR solution is the lowest, and its average bitterness scores at 0s, 15s and 60s are 3.9, 3.9 and 3.4 respectively. Compared with PNS solution, its entrance bitterness, peak bitterness and bitter aftertaste scores are reduced by nearly 50% respectively; compared with PNS-2.5% OLI, its entrance bitterness and peak bitterness are reduced by 31.6% and 32.8 respectively, and the aftertaste bitterness is reduced by 27.7%. Based on this, the effect of vibration mill grinding time on the effect of micro-κ-CAR coated PNS-OLI was further investigated, and the bitterness of PNS-OLI-CAR after grinding for 6, 9, 12, 15 and 18 minutes was evaluated. The results are as follows Figure 2 As shown in B, within 6 to 15 minutes, as the grinding time increases, the bitterness of PNS-OLI-CAR gradually decreases, indicating that micro-κ-CAR is coated on the surface of PNS-OLI to form a core-shell structure during the grinding process, and as the coating time increases, the core-shell structure tends to be complete, thereby significantly reducing the amount of PNS dissolved in the solution and significantly reducing the bitterness. However, when the grinding and coating is continued to 18 minutes, the bitterness of the PNS-OLI-CAR solution increases, indicating that too long grinding time will destroy the core-shell structure formed by micro-κ-CAR on the surface of PNS-OLI, thereby exposing the bitterness of PNS. Figure 2 B shows that the bitterness score of the PNS-OLI-CAR solution ground and coated for 15 minutes is the lowest. The average bitterness scores at 0s, 15s and 60s are 2.5, 2.8 and 2.7, respectively, which are slightly bitter. Compared with the PNS solution, the bitterness at each time point was reduced by 66.7%, 64.1% and 59.7%, respectively. In summary, the present invention successfully constructed PNS-OLI-CAR rapid-setting microcapsules, which can significantly reduce the bitterness of the entrance, peak bitterness and aftertaste of PNS, thereby improving the patient's medication compliance.
[0104] 1.2 Electronic tongue evaluation
[0105] Volunteer evaluation can best reflect the true taste of oral preparations, but it is highly subjective and there are large individual differences between different volunteers. Electronic tongue is a detection technology that uses the characteristic response signal of a chemical sensor array to simulate the human taste perception process. It has the advantages of objectivity, simplicity of operation, good repeatability, and low detection threshold. In recent years, electronic tongue has been widely used in the identification of the taste of traditional Chinese medicine and the evaluation of the taste of food. The electronic tongue results showed that the bitterness score of 10mg / ml PNS solution was 7.24, and the bitter aftertaste score was 1.76 points ( Figure 2 C). After PNS was wrapped with 2.5% and 5% OLI respectively, the bitterness score of PNS-OLI decreased, but there was no statistical difference. This is consistent with the evaluation results of volunteers, that is, OLI forms an oil film on the surface of PNS, which has a certain masking effect on the bitterness of PNS. The bitterness scores of PNS-2.5% OLI and PNS-5% OLI were 7.14 and 6.70, respectively, and the bitter aftertaste scores were 1.48 and 1.51, respectively. The results did not show a trend that the greater the amount of OLI, the better the bitterness masking effect, which is contrary to the evaluation results of volunteers. Therefore, the present invention screens the optimal molding process of PNS-OLI-CAR, and the combination of subjective and objective evaluation makes the research results more authentic and reasonable. Based on the evaluation of volunteers and the results of electronic tongue tests, the present invention selects PNS-OLI with a dosage of 2.5% OLI to construct PNS-OLI-CAR.
[0106] The bitterness of PNS-OLI-CAR was evaluated by electronic tongue to screen the optimal dosage ratio of micro-κ-CAR. The results showed that compared with PNS, the bitterness of PNS-OLI-CAR at different dosage ratios was significantly reduced, with bitterness scores ranging from 4.06 to 6.22 and bitter aftertaste scores ranging from 0.75 to 1.75. Similar to the evaluation results of volunteers, with the increase of micro-κ-CAR dosage, the bitterness score showed a trend of first decreasing and then increasing. Among them, at a dosage of 1:0.6 for PNS-OLI:micro-κ-CAR, the bitterness and bitter aftertaste scores of PNS-OLI-CAR were the lowest, which were 4.06 and 0.75, respectively. Compared with PNS, its bitterness was reduced by 44.6% and the bitter aftertaste was reduced by 57.4%. Within 6 to 15 minutes, as the coating time increased, the bitterness score of PNS-OLI-CAR also showed a downward trend, and the bitterness was between 4.01 and 4.70; but when the coating time was extended to 18 minutes, the bitterness score increased, which was consistent with the evaluation results of the volunteers. Among them, the bitterness masking effect of PNS-OLI-CAR coated for 15 minutes was the best, with bitterness and bitter aftertaste of 4.01 and 0.73 respectively, which also confirmed the above-mentioned volunteer evaluation results. In short, the present invention successfully constructed PNS-OLI-CAR rapid-setting microcapsules, which can significantly reduce the bitterness and bitter aftertaste of PNS.
[0107] 2. Drug loading and dissolution
[0108] 2.1 Drug loading and encapsulation efficiency
[0109] The maximum absorption wavelength of PNS measured in the UV-visible spectrophotometer is 219 nm, so the content of PNS is determined at this wavelength. The concentration is used as the horizontal axis and the absorbance is used as the vertical axis to obtain a standard curve Y=0.3983X+0.2433, R 2 =0.9992, indicating that the PNS concentration has a good linear relationship with the absorbance in the range of 0.625-5 mg / mL. The method has good stability, precision and repeatability, and its RSD values are 2.30%, 0.39% and 2.84%, respectively. The RSD value of the sample recovery rate is 3.60%, indicating that the method has high accuracy. The PNS-OLI-CAR rapid-setting microcapsules constructed by the present invention have a high drug loading capacity and encapsulation rate, which are 59.07±1.18% and 94.52±1.88% (n=3), respectively. This shows that micro-κ-CAR may be an ideal material for constructing rapid-setting microcapsules, and may also be an ideal carrier for encapsulating PNS.
[0110] 2.2 Dissolution
[0111] PNS-OLI-CAR quick-setting microcapsules need to achieve the purpose of less dissolution in the water-mouth and dissolution in the stomach, so as to cover up the bitter taste of PNS in the water-mouth and not interfere with its release in the stomach. Therefore, the present invention investigates the water ( Figure 3 A), simulated gastric fluid (pH 1.2) ( Figure 3 B) and simulated intestinal fluid (pH 6.8) ( Figure 3 C) and other three conditions. Figure 3 A It can be seen that within 5 minutes, the dissolution rate of PNS is 107.08% and has been completely dissolved, while the dissolution rate of PNS-OLI-CAR is 65.80%, indicating that the quick-setting microcapsules significantly inhibit the dissolution of PNS in water, thereby reducing its bitterness intensity in water-mouth, which also supports the above taste evaluation results. Within 2 hours, the cumulative dissolution rate of PNS-OLI-CAR is up to 78.31%, which is significantly lower than the maximum dissolution rate of PNS of 107.08%.
[0112] At pH 1.2 and 6.8 ( Figure 3B and C), the time for PNS to reach the maximum cumulative dissolution was 20min (90.97%) and 15min (74.50%), respectively, and then it showed a downward trend within 2h. Under pH 1.2 conditions, the solubility of PNS-OLI-CAR at 20min was 88.27%, and the dissolution curve of the first 20min basically coincided with the dissolution curve of PNS. It is worth noting that the cumulative dissolution of PNS-OLI-CAR after 20min showed an upward trend, and the cumulative dissolution at 2h was 100.07%, which was significantly greater than the dissolution of PNS. This shows that the construction of quick-setting microcapsules not only does not affect the solubility of PNS in the stomach, but also increases the solubility of the same dose of PNS in the stomach, thereby increasing the absorption and utilization of PNS and improving its bioavailability. Under pH 6.8 conditions, the time for PNS-OLI-CAR to reach the maximum cumulative dissolution was 20min (72.18%), which is basically consistent with the solubility of PNS under this condition. In the next 2 hours, the cumulative dissolution rate of PNS-OLI-CAR tended to be flat, and finally reached 70.65%, which was also greater than the dissolution rate of PNS.
[0113] In addition, compared with the pH 1.2 solution, the solubility of PNS in PNS-OLI-CAR in water and pH 6.8 solution is lower. It can be seen that the amount of PNS dissolved from the quick-setting microcapsules is affected by micro-κ-CAR and the pH value of the dissolution medium. One of the reasons speculated is that micro-κ-CAR absorbs water and swells without dissolving. After encountering water, it quickly gels on the surface of PNS-OLI-CAR to form a gel barrier layer, which reduces the release of PNS and achieves the purpose of reducing the bitterness of the solution. The second reason may be that there is an electrostatic interaction between micro-κ-CAR and PNS, which limits the dissolution and release of PNS in the medium. Compared with water and pH 6.8 dissolution medium, the cumulative release of PNS-OLI-CAR in pH 1.2 medium reaches 100%. The possible reason is that micro-κ-CAR is relatively stable in neutral and alkaline solutions and will not hydrolyze even if heated; but it is easy to hydrolyze in acidic solutions (especially pH ≤ 4.0), and the strength and viscosity of the gel layer are reduced, so that the PNS in the quick-setting microcapsules are completely exposed. In summary, the solubility of PNS-OLI-CAR in water and simulated intestinal fluid at pH 6.8 was low, but it could be dissolved and released normally in simulated gastric fluid at pH 1.2. This proves that the quick-setting microcapsules can mask the bitter taste of PNS in water-mouth without affecting its normal release in the stomach to exert its drug efficacy.
[0114] 3. Powder properties
[0115] 3.1 Average particle size and particle size distribution
[0116] The average particle size and particle size distribution of the four powders are shown in Figures (3B and C). (0.9) The d of PNS-OLI was 66.14 μm, 25.08 μm, 28.40 μm and 40.85 μm respectively. (0.9) Compared with PNS, it is reduced by 57.06%. Then, PNS-OLI was dry-ground and coated with micro-κ-CAR for 15 min. The d (0.9) Compared with PNS, it is reduced by 38.24%. However, compared with micro-κ-CAR and PNS-OLI, the d (0.9) Combined with the above taste evaluation and dissolution results, it can be proved that micro-κ-CAR is encapsulated on the surface of PNS-OLI to increase its particle size.
[0117] 3.2 Specific surface area and porosity
[0118] The specific surface area and porosity of the four samples are shown in Figure 3 D and Table 1, Figure 4 As shown. The isotherms of micro-κ-CAR and PNS-OLI-CAR are type III (IUPAC classification), indicating that their pore structures are irregular. The isotherms of PNS and PNS-OLI are close to type VI, reflecting the result of multilayer adsorption on a non-porous uniform solid surface. The pore diameters of the four samples are all in the range of 2 to 50 nm, which can be classified as mesopores. Among the four samples, micro-κ-CAR has the largest specific surface area and porosity, followed by PNS-OLI-CAR, PNS-OLI, and PNS. It can be seen that after OLI and micro-κ-CAR are successively coated on the surface of PNS, the specific surface area and porosity of the powder gradually increase, which is not only related to the reduction of its particle size, but also to the specific surface area and porosity of micro-κ-CAR. PNS is easily soluble in water, although the increase in specific surface area and porosity will cause it to dissolve quickly in water and expose its bitter taste. However, micro-κ-CAR swells but does not dissolve when it comes into contact with water, and its large specific surface area and porosity cause it to swell quickly into a gel state when it comes into contact with water. The present invention encapsulates micro-κ-CAR on the surface of PNS-OLI by dry powder coating to form a quick-setting microcapsule core-shell structure. After coming into contact with water, micro-κ-CAR forms a gel barrier layer on the surface to isolate PNS from water, thereby avoiding exposure to bitterness. The specific surface area and porosity of PNS-OLI-CAR are between those of PNS and micro-κ-CAR, which can prove that the micro-κ-CAR results are encapsulated on the surface of PNS-OLI, thereby increasing its specific surface area and porosity (tending to micro-κ-CAR).
[0119] Table 1. Specific surface area, porosity, average pore size and appearance of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR
[0120]
[0121] 3.3 Wettability and rapid setting
[0122] The time required for PNS-OLI-CAR to be completely wetted in pure water at different temperatures and at different stirring speeds is shown in Table 2. As can be seen from the table, as the stirring speed or water temperature increases, the wetting speed of PNS-OLI-CAR becomes faster. In pure water at 60°C with different stirring speeds, it can be wetted and dispersed within 15s. It is worth noting that no matter what the stirring speed is, it can be completely wetted and dispersed in pure water at 70°C within 10s. Even at 70°C and a stirring speed of 400rpm, it can be completely wetted and dispersed within 5s, indicating that the PNS-OLI-CAR quick-setting microcapsules have good quick-setting properties.
[0123] Table 2. Wettability of PNS-OLI-CAR at different water temperatures and stirring speeds
[0124]
[0125] Note: Compared with 50℃, **P<0.01
[0126] The stability analyzer was used to record the changes in the transmitted light (T) and stability parameters (TSI) of the four samples within 1 hour. Figure 5 ), which reflects the dispersibility and stability of the four powders in pure water, as well as the rapid setting performance of PNS-OLI-CAR rapid setting microcapsules. Figure 5A shows that the TSI value of PNS after being dispersed in water is the smallest (TSI < 10), and the stability is the best. This is because PNS is easily soluble in water, and the powder gradually dissolves to form a relatively stable transparent solution, so the system changes less. However, the stability of micro-κ-CAR and PNS-OLI is relatively poor (TSI ≥ 30), and the system changes more. This is because micro-κ-CAR absorbs water and swells into a colloid, especially when the powder just contacts water, the surface absorbs water quickly to form a gel barrier layer to isolate the internal powder from water to form a mass, which cannot be dispersed in water. After that, the internal powder continues to absorb water and swell, so the system is always in a state of change. The poor stability of PNS-OLI is because the powder is dispersed in water, and the presence of surface OLI makes the solution suspended, and the uniformity and stability of the system are poor, resulting in a large TSI value. The TSI value of PNS-OLI-CAR (≤15) is between that of PNS and micro-κ-CAR. The micro-κ-CAR on the surface of the quick-setting microcapsule quickly gels in water to form a gel barrier layer that isolates the internal PNS from water, forming a core-shell structure of the quick-setting microcapsule, which is then dispersed in water to form a relatively stable system. It is worth noting that the speed at which the gel barrier on the surface of the quick-setting microcapsule forms is comparable to the speed at which the PNS powder is dispersed in water ( Figure 5 A and B), which proves that it has good quick-setting and dispersibility in water.
[0127] The transmitted light graph shows the changes of the four powders in water within 1 hour. Figure 5 As can be seen from C and F, the T value intensity changes of PNS and PNS-OLI-CAR are similar, and the T value fluctuates around 80%. The T changes of the two mainly appear in the first 5 minutes at a height of 37.5-40 mm, which is 0. After 5 minutes, the T value at the bottom of the bottle (0-4 mm) is 0, and the change area has a certain upward shift compared to PNS. This shows that the rapid coagulation rate of PNS-OLI-CAR in water is equivalent to the dissolution rate of PNS in water. At the same time, due to the presence of micro-κ-CAR on the surface, its particle volume will absorb water and increase. Within 25 seconds, the T value of micro-κ-CAR at a height of 32.5mm-40mm is 0. After 25 seconds, the micelle gradually moves downward and reaches the bottom of the bottle (0-10mm) after 10 minutes. During this period, its T value is between 5% and 40%; then within 1 hour, its micelle swells and expands, and the T value changes in height ( Figure 5 D). The change in its T value reflects that the powder swells rapidly into micelles when it meets water and falls to the bottom of the bottle, and then continues to absorb water and swell, causing the volume to expand upward, so its T value has obvious changes in height. The change in the T value of PNS-OLI shows that the system is in a state of continuous change in the first 10 minutes of contact between the powder and water ( Figure 5E). The particle size of the particles is getting bigger and bigger, and its T value is getting smaller and smaller, decreasing from 70% to 10% within 1 hour. It is speculated that the reason is that after PNS-OLI is dispersed in water to form a suspension, the oil droplets aggregate, causing its particle size to increase and the T value to decrease.
[0128] 4. Structural characterization
[0129] 4.1 Optical microscopy
[0130] Figure 6 The microstructures of PNS-OLI and PNS-OLI-CAR observed by optical microscopy are shown. Figure 6 As can be seen from Figure C, the PNS-OLI powder is evenly distributed in water, the particle size is relatively uniform, the microstructure is spherical oil droplets, and the surface is smooth, which proves that OLI is encapsulated on the surface of PNS to form an oil film to prevent PNS from contacting water. The microstructure of PNS-OLI-CAR is still spherical ( Figure 6 D), the shape is regular and the structure is complete, but the surface morphology is obviously different from that of PNS-OLI. It is no longer a smooth oil droplet, but a spherical particle wrapped by a layer of white substance. It is speculated that the micro-κ-CAR on the surface of PNS-OLI-CAR quickly gels when it encounters water to form a white gel barrier. This proves that the present invention has successfully constructed a bitter quenching rapid-gelling microcapsule with a core-shell structure, which can encapsulate bitter substances and achieve bitterness shielding.
[0131] 4.2SEM and EDS
[0132] The SEM results of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR are shown in Figure 7 SEM of PNS Figure 7 A shows that it is irregular block with smooth and complete surface, so the specific surface area and porosity are small. The surface of micro-κ-CAR is rough and granular ( Figure 7 B), and there are obvious gaps, so the specific surface area and porosity are large. In the vibration mill, PNS and OLI are co-grinded and coated to obtain PNS-OLI. The powder particle size is reduced, but the surface is still smooth and complete, and small particles adhere to the surface of large particles ( Figure 7 C), so its specific surface area and porosity are increased compared with PNS. Then, micro-κ-CAR is added and co-grinded to obtain PNS-OLI-CAR, which is formed by extrusion and coating of particles and has an irregular shape, and the surface is no longer smooth ( Figure 7 D), but showed a rough granular shape similar to micro-κ-CAR, indicating that micro-κ-CAR was successfully encapsulated on the surface of PNS-OLI, so its specific surface area and porosity increased significantly compared with PNS. This is consistent with the above specific surface area and porosity experimental results.
[0133] EDS analysis results are as follows Figure 7 As shown, the C and O elements of PNS account for 68.95Wt% and 31.05Wt%, respectively ( Figure 7 A), while the C and O elements of PNS-OLI account for 71.04Wt% and 28.96Wt% respectively ( Figure 7 C). The increase in the C ratio and the decrease in the O ratio on the PNS-OLI surface prove that OLI is encapsulated on the PNS surface. The C, O, and S elements of micro-κ-CAR account for 25.42, 30.34, and 2.93Wt% respectively ( Figure 7 B), and also contains 8.82Wt% Si, 13.31Wt% Cl and 18.71Wt% K. The C, O and S elements of PNS-OLI-CAR account for 56.94, 28.35 and 2.21Wt% respectively ( Figure 7 D), and Si, Cl and K accounted for 1.88, 3.52 and 6.81 Wt%, respectively. Compared with PNS-OLI, the C ratio of PNS-OLI-CAR was significantly reduced, and elements such as S, Si, Cl and K appeared at the same time, indicating that micro-κ-CAR was successfully encapsulated on the surface of PNS-OLI.
[0134] 4.3 FTIR
[0135] The FTIR results of the four samples are as follows: Figure 8 As shown in A. The characteristic peaks of PNS include 3331cm -1 OH bond stretching vibration, 2924cm -1 The stretching vibration of the CH bond at 1642 cm -1 is the bending vibration of the OH bond, 1380cm -1 It is the CH stretching vibration of methyl group, 1070cm -1 and 1011cm -1 They are caused by the vibration of CO and COH, 890cm -1 =CH bond. Oli characteristic peaks: 3005, 2921cm -1 , 2852cm -1 , 1744cm -1 , 1463cm -1 , 1236cm -1 , 1159cm -1 , 721cm -1 , 2800~3100, 1700~1800, 900~1400 are the main peaks caused by CH stretching, C=O stretching, COC stretching and CH bending respectively. Micro-κ-Car characteristic peak: 3381cm -1is the -OH stretching vibration of the hydroxyl group, 1631 is the polymer bound water, 1219 cm -1 S=O ofsulfate esters, 925cm -1 is 3,6-anhydro-D-galactose, 842cm -1 It is D-galactose-4-sulfphate. PNS-Oli characteristic peak: 3333cm -1 , 2924cm -1 , 1744cm -1 , 1642cm -1 , 1380cm -1 , 1070cm -1 , 1012cm -1 , 890cm -1 The PNS characteristic peak has no obvious change or displacement, but the characteristic peak 2924cm -1 The peak intensity of 1744 cm-1 increased with the addition of olive oil. -1 (C=O). PNS-Oli-Car characteristic peak: 3329cm -1 , 2924cm -1 , 1641cm -1 , 1381cm -1 , 1224cm -1 , 1068cm -1 , 1023cm -1 , 925cm -1 , 843cm -1 The characteristic peak of PNS is 1011cm -1 (hydroxyl group) moves to 1023 cm -1 , characteristic peak 890cm -1 (=CH) is significantly weakened; the characteristic peak of OLI is 1745cm -1 (C=O) disappears; the characteristic peak of micro-κ-Car appears at 925cm -1 and 842cm -1 , and the characteristic peak 1219cm -1 (Sulfate ester group) moves to 1224cm -1 , and the peak intensity weakened, indicating that there may be intermolecular forces in PNS-Oli-Car. It is speculated that there may be electrostatic interactions between the alcohol hydroxyl groups in PNS and the sulfate groups in micro-κ-CAR, and all characteristic peak intensities of PNS-Oli-Car are weakened, and hydrogen bonds may be formed between molecules.
[0136] 4.4 Raman
[0137] The Raman spectra of the four samples are shown in Figure 2. Figure 8 B. PNS at 2938cm -1 and 1384cm -1 The characteristic peaks at 1678 cm represent C=C stretching, 1454 cm -1 The absorption peak at 1122 cm is the C=C stretching on the fatty chain. -1 The characteristic peak at 523 is the stretching of the COC bond, and the peak at 3006 is the "breathing" vibration peak of the six-membered carbon ring. The absorption peaks of micro-κ-CAR at 3006 and 2932 are CH stretching, the characteristic peak at 849 (strong) is the vibration of COS (D-galactose-4-sulfphate), 933 (weak) is 3,6-anhydro-D-galactose, 1258 is S=O sulfate, 1354 is C=O and COH, and 1000-1100 is the link of the glycosidic bond. OLI at 2918-2877 is CH stretching, 1753 is C=O bond stretching vibration, 1660 is C=C stretching vibration, 1443 is CH stretching, 1303 is CH bond bending vibration, and 1269 is =CH bending vibration. PNS-OLI: The absorption peak at 2957 is CH stretching, 1678 and 1455 are the same as PNS, and 1122 is the same as PNS, indicating that the addition of olive oil only physically isolates the bitter taste and does not produce an interaction with PNS. PNS-OLI-CAR is CH stretching at 2938-2964, 1680 and 1456 are the same as PNS, the characteristic peak COC bond at 1126 changes from a sharp peak to a flat peak, the intensity of the characteristic peak D-galactose-4-sulfphate at 849 is weakened, and the characteristic peak 3,6-anhydro-D-galactose at 933 moves to 929. The most important thing is that a new characteristic peak appears at 1364, indicating that micro-κ-CAR may interact with PNS, which is consistent with the above FTIR results. The intensity of the characteristic peaks of PNS in PNS-OLI-CAR is weakened, indicating that it may be encapsulated in micro-κ-CAR. At the same time, the characteristic peak shift and peak intensity of micro-κ-CAR are weakened, which may be an interaction between it and PNS.
[0138] 4.5DSC
[0139] The DSC data of each sample are shown in Figure 8C. The endothermic peak of micro-κ-CAR at 124℃ is caused by the loss of bound water in micro-κ-CAR. The exothermic peak at 220℃ may be caused by the degradation / decomposition of the CAR structure. The endothermic peak of PNS at 98℃ is due to the loss of bound water in PNS. The endothermic peak at 211℃ indicates melting. The exothermic peak of OLI at 270℃ indicates oxidation / decomposition. The endothermic peak of PNS-OLI at 115℃ indicates the loss of water, and the increase in temperature indicates that the encapsulation of OLI improves the thermal stability of PNS. The endothermic peak at 213℃ is caused by the melting of PNS. The exothermic peak at 274℃ is caused by the oxidation / decomposition of OLI. The endothermic peak of PNS-OLI-CAR at 120℃ indicates the loss of water in the structure, and it has better stability than PNS. The exothermic peak at 209℃ may be due to the decomposition of the structure of micro-κ-CAR wrapped on the surface of PNS. The endothermic peak at 211°C was caused by the melting of the inner layer PNS. The above results show that during the thermal decomposition of PNS-OLI-CAR, PNS melted only after the decomposition of micro-κ-CAR, proving that micro-κ-CAR was successfully coated on the surface of PNS and improved the thermal stability of PNS.
[0140] 4.6XPS
[0141] Figure 8 D represents the full scan of XPS analysis of PNS, micro-κ-CAR, PNS-OLI and PNS-OLI-CAR, and Table 3 represents the atomic concentration of narrow scan. The results show that the PNS sample contains 66.43% C1s and 33.57% O1s. The micro-κ-CAR sample contains 18.11% C1s, 75.46% O1s and 6.43% S2p. After wrapping PNS with OLI, the proportion of C1s in the PNS-OLI sample increases and the proportion of O 1s decreases, accounting for 83.33% and 16.67%, respectively. This is because the proportion of C in OLI is much greater than that of O, so the proportion of C and O on the surface of PNS-OLI approaches it. After PNS-OLI is wrapped by micro-κ-CAR, the PNS-OLI-CAR sample contains 70.57% C1s, 28.51% O1s and 0.92% S2p. Compared with PNS-OLI, its C1s ratio decreased, O 1s ratio increased, and S2p also existed, which was consistent with the above EDS results, proving that micro-κ-CAR was successfully wrapped on the surface of PNS-OLI. In addition, compared with C1s and O1s of PNS, the binding energy of C1s and O1s of PNS-OLI-CAR increased by 0.1eV and 0.11eV, respectively, which may be due to the sequential wrapping of micro-κ-CAR on the surface of PNS, or it may be due to the reduction of the electron cloud density around the C atom.
[0142] Table 3. Binding energy and surface elemental composition of PNS, micro-κ-CAR, PNS-OLI, and PNS-OLI-CAR measured by XPS spectra
[0143]
[0144] Fig. 9 The narrow scan XPS graphs among the four samples in different binding energy ranges are shown. In the XPS C 1s spectrum of PNS, the peaks at 284.80, 286.51 and 287.96 eV correspond to CC, CO and C=O, respectively, and the peak at 532.95 eV in the O 1s spectrum is COC. In the XPS C 1s spectrum of PNS-OLI, the peaks at 284.80, 286.51 and 288.86 eV correspond to CC, CO and C=O, respectively, while the peaks at 532.65 and 533.59 eV in the O1s spectrum correspond to COC and COH, respectively. Compared with PNS, the binding energy of the C=O bond in PNS-OLI is enhanced, the binding energy of the COC bond is reduced, and the COH bond also exists, indicating that the electron cloud density around the atoms has changed. In the XPS C 1s spectrum of micro-κ-CAR, the peaks at 284.80, 286.36 and 287.79 eV correspond to CC, CO and C=O, respectively, the peak at 532.58 eV in the O 1s spectrum is COC, and the peaks at 168.43 and 169.53 in the S2p spectrum are S2p3 and S2p1, respectively. In the XPS C 1s spectrum of PNS-OLI-CAR, the peaks at 284.80, 286.48 and 287.84 eV correspond to CC, CO and C=O, respectively, the peak at 532.84 eV in the O 1s spectrum is COC, and the peaks at 168.85 and 169.95 eV in the S2p spectrum are S2p3 and S2p1, respectively. Compared with micro-κ-CAR, the binding energy of the C1S and O1s chemical bonds in PNS-OLI-CAR is between PNS and micro-κ-CAR, and the binding energy of S2p3 is higher than that of CAR, indicating that the electron cloud density around the C, O, and S atoms has changed. The change in electron cloud density may be due to the interaction between molecules.
[0145] 4.7AFM
[0146] The morphologies of PNS, micro-κ-CAR, PNS-OLI and PNS-OLI-CAR were observed by AFM. Fig.10). As shown in the figure, PNS powder is evenly dispersed in water in the form of spherical particles, without obvious aggregation, and the surface roughness is 0.651nm (Ra). However, the uneven dispersion of micro-κ-CAR powder in water leads to small particle aggregation, and the surface roughness is 60.1nm (Ra). This is because micro-κ-CAR powder does not dissolve in water, but only absorbs water to swell into gel, and has a certain degree of adhesion. PNS-OLI powder can be dispersed in water in the form of spheres, and the surface oil film causes ripples on the observed particle surface ( Fig.10 ), which also proves that OLI is successfully wrapped on the surface of PNS. Compared with PNS, the roughness of PNS-OLI is significantly increased, with a value of 1.91nm (Ra), which may be due to the increase in surface roughness caused by the addition of oxygen-containing compounds. Fig.10 It can be seen that the morphology of PNS-OLI-CAR is similar to that of micro-κ-CAR powder, mainly in the form of small particles, but there is also a certain amount of aggregation, which may be due to the adhesion of surface carrageenan absorbing water to form a gel, resulting in particle aggregation. Its roughness is 61.0nm (Ra), which is close to that of micro-κ-CAR. Fig.10 It can be seen that its morphology is similar to that of PNS, uniformly dispersed in water in a granular form, with a surface roughness of 4.94nm (Ra). Compared with PNS and PNS-OLI, the roughness of PNS-OLI-CAR is significantly increased. This difference is caused by the oxygen atoms in micro-κ-CAR. In short, the AFM results show that PNS-OLI-CAR has a passion fruit seed-like bionic structure after contact with water, that is, the inside is PNS drug, the middle is a thin OLI oil layer, and the outer layer is a micro-κ-CAR gel layer. This also proves that the micro-κ-CAR capsule material can form a gel barrier layer on the drug surface after contacting water to prevent the drug from dissolving and exposing the bitter taste, thereby achieving the purpose of physically shielding the bitter taste of the capsule core drug.
[0147] 5. Quantum Chemistry
[0148] Fig.11The two binding sites and electrostatic potential strengths of the three main bitter-contributing components in PNS, ginsenosides Rg1, Rb1 and Rd, respectively, reacting with κ-CAR are shown. Binding energy (E) can be used to measure the stability of a molecule or molecular complex. If the binding energy is negative, it indicates that the energy of the system is reduced, and the larger the absolute value of the binding energy, the more stable the complex. The change in Gibbs free energy (ΔG) can predict whether a process is spontaneous. It is generally believed that when ΔG is less than 0, the reaction can proceed spontaneously, and the larger the absolute value, the easier it is for the reaction to occur. The results of quantum chemical calculations show that Rg1 binds to κ-CAR mainly in the form of site 2, because its E value and ΔG value are relatively lower. This not only shows that the reaction between the two is spontaneous, but also that the two bind more tightly and more stably at site 2. At this site, κ-CAR is located in the groove of Rg1, and the -OH of Rg1 is closer to the sulfate group of κ-CAR. Rb1 binds to κ-CAR mainly in the form of site 1. This is because Rb1 has a very obvious groove at site 1, and κ-CAR can be tightly stuck, so the two bind more tightly and stably at site 1 (E value and ΔG value are relatively lower). The E value and ΔG value of Rd and κ-CAR at site 1 are relatively lower, indicating that the two bind more tightly and stably here. It is worth noting that the sites where Rg1, Rb1 and Rd bind more tightly to κ-CAR all show that the -OH in the bitter component structure is closer to the sulfate group of κ-CAR, and the molecular size of κ-CAR is more matched with the groove size of the bitter component, which may be the reason why κ-CAR has a significant bitterness-suppressing and taste-masking effect on PNS.
[0149] The darker the blue in the system, the greater the positive value of the electrostatic potential and the more positive charges are distributed; while the darker the red, the greater the negative value of the electrostatic potential and the more negative charges are distributed. Fig.11 It shows that most areas in the Rg1, Rb1 and Rd systems are positively charged, especially around -OH, with a strong positive electrostatic potential. The κ-CAR system as a whole carries a large amount of negative charge, and the electrostatic potential around the sulfate group is the most negative. When the three bitter components bind to κ-CAR respectively, electrical neutralization occurs. The surface electrostatic potentials of Rg1, Rb1 and Rd at the two binding sites are all reduced, especially the electrostatic potential around -OH is significantly weakened, while the electrostatic potential around the sulfate group of κ-CAR is significantly enhanced. Among the three main bitter components, the surface electrostatic potential of Rb1 is reduced most significantly, and its absolute values of E value and ΔG value are also the largest, indicating that κ-CAR is most likely to react with it, and the stability of the system after binding is the strongest. The above results show that there are intermolecular electrostatic interactions between the three bitter components and κ-CAR, and the -OH of the bitter components and the sulfate group of κ-CAR are important groups.
[0150] In summary, the mechanism by which κ-CAR inhibits the bitterness of PNS may be related to the electrostatic interaction between the two, which reduces the electron cloud density of the -OH positively charged group in the three bitter components, reduces the distribution of positive charges, weakens the electrophilicity, and thus fails to activate the bitter receptors normally. This also verifies the above-mentioned FTIR, Raman, XPS and other analysis results, that is, there is an electrostatic interaction between κ-CAR and PNS. In addition, κ-CAR molecules can bind to the grooves in the three main bitter components in PNS, which may also prevent the bitter components from binding to the bitter receptors, thereby inhibiting the bitterness of PNS. Combined with the above AFM results, it can be seen that the quick-gel microcapsules can achieve the unification of the dual bitterness inhibition functions of physical shielding and electrostatic induction.
[0151] In summary, the present invention successfully constructed PNS-OLI-CAR quick-setting microcapsules, which are a new preparation with dual bitterness suppression functions. It can achieve the purpose of less dissolution in the water-mouth to suppress bitterness and mask taste, and fully exert the drug effect in the stomach. The optimal ratio and preparation process of PNS-OLI-CAR are to grind and coat PNS and 2.5% OLI in a vibration mill for 3 minutes, then add micro-κ-Car at a ratio of PNS-OLI and micro-κ-Car1:0.6, and continue grinding and coating for 15 minutes. The particle size of PNS-OLI-CAR quick-setting microcapsules is about 40μm, and the drug loading and encapsulation efficiency are 59.0% and 94.5%, respectively. In water at 60℃ and 70℃, the quick-setting microcapsules can be completely wetted and dispersed within 15s and 10s, respectively. The results of stability analysis show that its quick-setting speed in water is comparable to the speed at which PNS is dispersed in water, indicating that it has good quick-setting and dispersibility. Compared with PNS solution, the evaluation results of volunteers showed that the bitterness, peak bitterness and aftertaste of PNS-OLI-CAR quick-setting microcapsules were reduced by 66.7%, 64.1% and 59.7% respectively; the results of electronic tongue detection showed that its bitterness and bitter aftertaste were reduced by 44.6% and 58.5% respectively. This proves that quick-setting microcapsules have a good bitterness suppression and taste masking effect, and can be used to improve the unpleasant taste of bitter drugs, thereby improving patients' medication compliance.
[0152] The powder of PNS-OLI-CAR quick-setting microcapsules is irregular in shape, with a rough and granular surface, but it is dispersed in water as regular spherical particles with a white gel barrier layer on the surface and a thin OLI oil layer in the middle. Both the microstructure and SEM images can prove that micro-κ-CAR is successfully coated on the surface of PNS / PNS-OLI, and finally forms quick-setting microcapsules with a core-shell structure. The results of EDS and XPS analysis show that PNS-OLI-CAR is composed of capsule core PNS, a thin OLI oil layer in the middle, and capsule material micro-κ-CAR, and OLI is coated on the surface of PNS, and micro-κ-CAR is coated on the surface of PNS-OLI. The results of DSC and AFM tests both confirm the above conclusions, that is, micro-κ-CAR and OLI are successfully coated on the surface of PNS in turn to form a core-shell structure of PNS-OLI-CAR quick-setting microcapsules, which not only improves the thermal stability of PNS, but also avoids the dissolution of PNS in water and the exposure of bitterness. The results of FTIR, Raman and XPS analysis showed that there might be electrostatic interaction or intermolecular hydrogen bonding between PNS and micro-κ-CAR, and the electron cloud density around C, O, and S atoms in PNS-OLI-CAR changed. These conclusions were confirmed by the results of quantum chemical calculations, that is, there was indeed an electrostatic interaction between the three main bitter components in PNS and κ-CAR. κ-CAR can not only reduce the electron cloud density of the -OH positive point group in the bitter component, so that it cannot normally activate the bitter receptor to produce bitterness; it can also bind to the groove in the bitter component, thereby preventing it from binding to the bitter receptor to inhibit bitterness. The structural characterization of the quick-gel microcapsule not only proves that the quick-gel microcapsule has a bionic structure similar to passion fruit seeds, but also has the dual bitterness-suppressing taste-masking function of physical shielding and electrostatic induction, and also clarifies the mechanism of the quick-gel microcapsule in suppressing bitterness and masking taste.
[0153] In summary, the present invention proposes and successfully constructs a new preparation of quick-setting microcapsules for the first time, aiming to achieve the ideal taste-masking effect of drug powder in water-mouth, and solve the common problem of difficulty in taking medicines faced by children, the elderly and other groups. The present invention not only proves the bitterness-suppressing and taste-masking effects of quick-setting microcapsules, but also clarifies its dual bitterness-suppressing mechanism. Most importantly, compared with the preparation method of traditional microcapsules, quick-setting microcapsules are constructed through powder modification technology and particle design technology, avoiding the introduction of organic reagents and the dissolution of water-soluble drugs to release bitterness. Its preparation process is simple and has good repeatability. It can be used to improve the taste of other bitter drugs, and it can also provide new ideas and strategies for the development and application of other bitter drug preparations.
Claims
1. A bitter quenching quick-setting microcapsule, characterized in that: It is composed of a bitter drug containing -OH as the capsule core, a thin oil layer in the middle, and micro-κ-Car as a quick-setting microcapsule material.
2. The bitter quenching quick-setting microcapsule according to claim 1, characterized in that: The bitter medicine containing -OH includes notoginseng total saponin, berberine, quercetin, naringin, limonin and momordica charantia. The oil layer is olive oil, camellia oil, corn oil, rapeseed oil, soybean salad oil and peanut oil.
3. The bitter quenching quick-setting microcapsule according to claim 1 or 2, characterized in that: It uses powder modification technology and particle design technology to coat the gel powder coating material on the surface of drug powder to construct quick-setting microcapsules.
4. The bitter quenching quick-setting microcapsule according to claim 2 or 3, characterized in that: The bitter drug is Panax notoginseng total saponin; the oil is olive oil; the weight ratio of Panax notoginseng total saponin, olive oil and micro-κ-Car is: 300 parts of Panax notoginseng total saponins, 7.5-15 parts of olive oil, and 180-300 parts of micro-κ-Car.
5. The bitter quenching quick-setting microcapsule according to claim 4, characterized in that: The weight ratio of the notoginseng total saponins, olive oil and micro-κ-Car is: 300 parts of Panax notoginseng total saponins, 7.5 parts of olive oil, and 180 parts of micro-κ-Car.
6. A method for preparing the bitter quenching quick-setting microcapsules according to claim 4 or 5, characterized in that: It includes the following steps: a. Take Panax notoginseng total saponins and olive oil, add them into a vibrating grinding hopper, and grind and coat for 3 minutes; b. Add the inclusion complex PNS-OLI and micro-κ-CAR prepared in step a into a vibrating grinding hopper, grind and coat for 6-18 minutes, and obtain bitter quenching rapid-setting microcapsules.
7. The method for preparing the bitter quenching quick-setting microcapsules according to claim 6, characterized in that: The amount of olive oil in step a is 2.5%-5% of the total amount of notoginseng total saponins and olive oil; The dosage ratio of PNS-OLI and micro-κ-CAR described in step b is: 1:(0.5-1); the grinding time is 15 minutes.
8. The method for preparing the bitter quenching quick-setting microcapsules according to claim 7, characterized in that: The amount of olive oil used is 2.5% of the total amount of Panax notoginseng saponins and olive oil; the dosage ratio of PNS-OLI and micro-κ-CAR described in step b is: 1:0.
6.
9. The method for preparing the bitter quenching quick-setting microcapsules according to any one of claims 6 to 8, characterized in that: The vibration mill coating conditions are: the machine operating temperature is -5°C, an appropriate amount of liquid nitrogen is added, the medium filling rate is 70%, the diameter is 21mm, and the columnar stainless steel medium has an amplitude of 6mm.
10. An oral preparation, characterized in that: Contains the bitter quenching quick-setting microcapsule according to any one of claims 1 to 5; preferably, the oral preparation is a tablet, powder, capsule or pill.